One-Pot Sequential Multistep Transformation of α,β-Unsaturated Trifluoromethyl Ketones: Facile Synthesis of Trifluoromethylated 2-Pyridones - Lv, Ning; Tian, Yi-Qiang; Zhang, Fa-Guang; Ma, Jun-An (Synlett, 2019)
A one-pot transformation of α,β-unsaturated trifluoromethyl ketones with 2-(phenylsulfinyl)acetamide to give trifluoromethylated 2-pyridones is realized. The reaction proceeds under mild conditions and involves multiple steps in an expeditious and controlled sequence to provide efficient access to a broad range of trifluoromethylated 2-pyridones in moderate to high yields. Moreover, further synthetic manipulations permit the routine synthesis of a diverse array of trifluoromethylated pyridines with good efficiency.
Keywords: trifluoromethyl group; pyridones; trifluoromethylpyridines; one-pot synthesis; multistep reaction